O60 The burden of opiates on irritable bowel syndrome with constipation patients diagnosed in secondary care. (19th June 2022) - Lewis-Lawson, Tilly; Isherwood, Grace; Bush, Debbie; Card, Tim; Corsetti, Maura
Abstract : Introduction: Opioid prescriptions in the UK are rising alarmingly. Opioid-induced constipation has been reported to affect around 2% of the UK population (Palsson OS et al, Gastroenterol 2020). Data from the USA suggests that opioid intake is higher in patients with functional bowel disorders and this associates with an increase in health care utilization (Hasler WL et al, Clin Gastroenterol Hepatol 2019). No previous studies have evaluated whether this is the case in the specific subgroup of patients who have irritable bowel syndrome with constipation (IBS-C). We aim to evaluate the percentage of patients taking opioids, their demographic characteristics, symptoms, and health-care utilization as compared to non-opioid using patients among those diagnosed with IBS-C by a single secondary care centre in the UK. Methods: Data recorded in clinical letters and on the hospital system from 257 IBS-C patients was retrospectively analysed and compared between patients taking and not taking opioids. Patients were diagnosed according to the Rome Criteria definition of the presence of abdominal pain or discomfort related to altered bowel habit. Results: 27.2% of IBS-C patients were taking opioids. These patients were older (49.1 ± 16.1, P<0.02), taking more medications (7.44 ± 4.2, P<0.001), had more hospital admissions not relating to their gastrointestinal issue (2.86 ± 4.2, P<0.03) and were more likely to have fibromyalgia (P<0.001) as compared to those not taking opioids. They also presented more frequently with abdominal pain (P<0.05) and dysphagia (P<0.04). 35% of patients taking opioids stopped and 54.55% of them experienced symptom improvement after this. Conclusions: This is the first study assessing the burden of opioid intake in IBS-C patients in the UK. The results show that almost one third of IBS-C patients are taking opioids, which associate with increased use of medications and hospital admissions. Interventions such as educational resources addressing appropriate opioid prescribing and the side-effects they can cause could benefit many patients with IBS-C in the future.